2015
DOI: 10.1038/jcbfm.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Age-Dependent Decrease in Dopamine D3 Receptor Availability: A [11C]-(+)-PHNO and [11C]-Raclopride Positron Emission Tomography Study

Abstract: Positron emission tomography with antagonist radiotracers has showed that striatal dopamine D 2/3 receptor (D 2/3 R) availability decreases with age. However, no study has specifically assessed whether D 2/3 R availability decreases with age in healthy persons as measured with agonist radiotracers. Moreover, it is unknown whether D 3 R availability changes with age in healthy humans. Thus, we explored the relationship between age and D 2/3 R availability in healthy humans using the 11 C]-Raclopride, negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
4
23
1
Order By: Relevance
“…These findings were confirmed in a whole-brain voxel-wise analysis and are largely consistent with previous studies finding age-related differences in the striatum (Nakajima et al, 2015). ROI analysis did not find age-related changes in in the high-binding extrastriatial areas of the SN/VTA and hypothalamus; however, whole-brain analysis identified regions of the midbrain where BP ND was positively associated with age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were confirmed in a whole-brain voxel-wise analysis and are largely consistent with previous studies finding age-related differences in the striatum (Nakajima et al, 2015). ROI analysis did not find age-related changes in in the high-binding extrastriatial areas of the SN/VTA and hypothalamus; however, whole-brain analysis identified regions of the midbrain where BP ND was positively associated with age.…”
Section: Discussionsupporting
confidence: 92%
“…Despite these tracer dissimilarities, the current results of receptor availability decline with age show no differences in the net measurement of age effects when compared to previously studied ligands. This suggests a D 2 R specific mechanism in the dorsal striatum, similar to previous findings with [ 18 F]NMB and [ 11 C](+)PHNO (Eisenstein et al, 2012; Nakajima et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, this work demonstrated that OB individuals exhibited higher D 2/3 Rs in both extrastriatal (ie, SN/VTA and pallidum) and striatal (ie, VST) regions associated with reward and motivation with the latter finding being the first published difference in any addiction-like condition with [ 11 C](+)PHNO in the striatum. These results were unaffected by adjustment for potential confounding factors such as age (Ishibashi et al, 2009;Kim et al, 2011;Matuskey et al, 2016;Nakajima et al, 2015;Volkow et al, 2000) or tracer injection parameters, and were confirmed with a whole-brain voxel-wise analysis. Moreover, after adding a cohort of OW individuals, we observed a positive linear association between BMI and D 2/3 R availability in the aforementioned regions that also persisted after adjusting for age, gender, and tracer injection parameters.…”
Section: Discussionmentioning
confidence: 61%
“…Notably, BP ND in the GP appears distinct from other regions. For example, [ 11 C]-raclopride BP ND in the GP was not found to be related to age, as it is for the other striatal ROIs (Nakajima et al, 2015). We contend that this is a valid ROI with [ 11 C]-raclopride and note that for the current investigation, GP BP ND was found to be differentially related to personality traits compared to nearby structures, such as the putamen.…”
Section: Discussionmentioning
confidence: 89%